(3x+y)(x-2y)=

Simple and best practice solution for (3x+y)(x-2y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+y)(x-2y)= equation:


Simplifying
(3x + y)(x + -2y) = 0

Multiply (3x + y) * (x + -2y)
(3x * (x + -2y) + y(x + -2y)) = 0
((x * 3x + -2y * 3x) + y(x + -2y)) = 0

Reorder the terms:
((-6xy + 3x2) + y(x + -2y)) = 0
((-6xy + 3x2) + y(x + -2y)) = 0
(-6xy + 3x2 + (x * y + -2y * y)) = 0
(-6xy + 3x2 + (xy + -2y2)) = 0

Reorder the terms:
(-6xy + xy + 3x2 + -2y2) = 0

Combine like terms: -6xy + xy = -5xy
(-5xy + 3x2 + -2y2) = 0

Solving
-5xy + 3x2 + -2y2 = 0

Solving for variable 'x'.

Factor a trinomial.
(x + -2y)(3x + y) = 0

Subproblem 1

Set the factor '(x + -2y)' equal to zero and attempt to solve: Simplifying x + -2y = 0 Solving x + -2y = 0 Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. x + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 x + 0 = 0 + 2y x = 0 + 2y Remove the zero: x = 2y Simplifying x = 2y

Subproblem 2

Set the factor '(3x + y)' equal to zero and attempt to solve: Simplifying 3x + y = 0 Solving 3x + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 3x + 0 = 0 + -1y 3x = 0 + -1y Remove the zero: 3x = -1y Divide each side by '3'. x = -0.3333333333y Simplifying x = -0.3333333333y

Solution

x = {2y, -0.3333333333y}

See similar equations:

| 5x-15=2y+12 | | 2(x+3)=7(x+2)+2 | | x+(x-3)=8 | | (4y-5)(8+y)=0 | | 24-(x+9)=9x-5 | | 5(2x+3c)= | | 4x+1=3x | | 4x-3=20x+1 | | 3x=4x+1 | | 28x+49=-3x | | 8x-(2x+9)=8x-31 | | 2x+20=x+25 | | 7p+6=9+6p | | 4m+5=36 | | (7+2)(7-2)+13= | | (12z-4)-(8+2z)=(2-3z)-(z-12) | | 8-10=z/9 | | 17-6+2(3d+2)= | | 3=m+11 | | 2x^2+5-11x=0 | | 5x-3(x-5)=17 | | 4x+17-3x=-6-10 | | 17-43=3(x-1)-8 | | X-3+2x+4+5x+11=180 | | r+5=10 | | 9x=3(6x+21) | | t-2(3-2t)=2+9 | | -3x+3=-45 | | 7x+4y=6 | | 27+4y-8=13y-9-2y | | 4y-3[x-2(3-2x)-4y]= | | 8x-3=11x-12 |

Equations solver categories